Pemanfaatan Batu Sungai Pattunuang Kabupaten Maros Pada Campuran AC-BC - Yerikho Esak Panggalo; Alpius; Louise Elizabeth Radjawane (Paulus Civil Engineering Journal, 2022)
In the transportation of the development of road-building and improvements are also increasing for the welfare of the community. This research aims to find out how the aggregate characteristics of the Pattunuang River of Maros Regency, asphalt characteristics, weight of filler types, and mixed characteristics. The method used is the conventional Marshall method to obtain the properties of the mixture, Marshall Immersion to obtain Marshall Stability from the remaining mixtures. The results of the study showed that the characteristics of pavement materials in the form of Pattunuang River Stone Maros Regency meet the technical requirements as a pavement material. Through the design of the mixture AC-BC coarse aggregate 42.82%, fine aggregate 45.73%, filler 5.45% dan optimum asphalt rate 6.00%. The mixed properties of AC-BC are Stability, flow, VIM, VMA, and VFB that meet the Bina Marga Specification 2018. Through testing Marshall Immersion mix AC-BC with Aspal Optimum content of 6.00% obtained Residual Marshall Stability of 91.69 % meets Bina marga specification 2018 at least 90%.